1975
DOI: 10.1680/geot.1975.25.3.555
|View full text |Cite
|
Sign up to set email alerts
|

The design, construction and performance of Cow Green embankment dam

Abstract: The 25 m high Cow Green embankment dam has been constructed in the upper Pennines on a deep boulder clay foundation with the aid of sand drains. The design of the core and filter received special attention following erosion of the rolled clay core of a neighbouring dam. The embankment design was based on a conventional factor of safety of 1·5. The sand drains did not achieve the predicted performance and the factor of safety in terms of effective stress approached 1·0 at completion. This condition does not rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…J.L. Sherard (1973) указал, что при определенных условиях давление, действующее на верхнюю часть плотины, может вызвать открытие существующих закрытых трещин или создать новые трещины [12,13]. Автор предположил, что ГР в ядре может произойти всякий раз, когда суммарные главные напряжения на определенной отметке в ядре достаточно низки по сравнению с давлением воды на той же отметке.…”
Section: предлагаемые критерии гидравлического разрыва в грунтовой пл...unclassified
See 1 more Smart Citation
“…J.L. Sherard (1973) указал, что при определенных условиях давление, действующее на верхнюю часть плотины, может вызвать открытие существующих закрытых трещин или создать новые трещины [12,13]. Автор предположил, что ГР в ядре может произойти всякий раз, когда суммарные главные напряжения на определенной отметке в ядре достаточно низки по сравнению с давлением воды на той же отметке.…”
Section: предлагаемые критерии гидравлического разрыва в грунтовой пл...unclassified
“…J.L. Sherard (1973) pointed out that, under certain conditions, the pressure acting on the top of a dam can cause the opening of existing closed cracks or create new cracks [12,13]. The author suggested that HF in the core can occur whenever the total principal stresses at a cer-tain elevation in the core are sufficiently low compared to the water pressure at the same elevation.…”
Section: Proposed Criteria For Hydraulic Fracture In a Groundwater Dammentioning
confidence: 99%